2007
DOI: 10.1063/1.2749200
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence decay time and electroluminescence of p-Si∕β-FeSi2 particles∕n-Si and p-Si∕β-FeSi2 film∕n-Si double-heterostructures light-emitting diodes grown by molecular-beam epitaxy

Abstract: We have epitaxially grown Si/ ␤-FeSi 2 /Si ͑SFS͒ structures with ␤-FeSi 2 particles on Si͑001͒, and SFS structures with ␤-FeSi 2 continuous films on both Si͑001͒ and Si͑111͒ substrates by molecular-beam epitaxy. All the samples exhibited the same photoluminescence ͑PL͒ peak wavelength of approximately 1.54 m at low temperatures. However, the PL decay times for the 1.54 m emission were different, showing that the luminescence originated from different sources. The decay curves of the SFS structures with ␤-FeSi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…6(b). This value (118 meV) is comparable to reported data of b-FeSi 2 embedded in p-n junctions, fabricated by cryogenic ion implantation [8] and by MBE [17]. It is also thought to be very different from the reported thermal quenching energies of 7-12 meV for the dislocation-related D1 emission and 4-10 meV for the dislocation-related D2 emission [26,27].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…6(b). This value (118 meV) is comparable to reported data of b-FeSi 2 embedded in p-n junctions, fabricated by cryogenic ion implantation [8] and by MBE [17]. It is also thought to be very different from the reported thermal quenching energies of 7-12 meV for the dislocation-related D1 emission and 4-10 meV for the dislocation-related D2 emission [26,27].…”
Section: Resultssupporting
confidence: 84%
“…We demonstrate the luminescent properties of strained b-FeSi 2 precipitates in Si and can get some consistent results on the origin of b-FeSi 2 luminescence. Temperature dependence of electroluminescence from b-FeSi 2 is usually utilized to study its thermal quenching [17]. For the MOS tunnel diode, the injection current can be maintained at low temperature without changing the applied voltage due to the tunneling nature of the carrier injection [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…b-FeSi 2 has been fabricated by various growth techniques such as ion beam synthesis (IBS), reactive deposition epitaxy (RDE), molecular-beam epitaxy (MBE) and magnetron-sputtering deposition. Epitaxial growth of b-FeSi 2 occurs in its initial nucleation stage by RDE [4,5]. However, the nucleation is different for ion-beam-synthesized b-FeSi 2 .…”
Section: Introductionmentioning
confidence: 98%
“…At present, semiconducting iron disiliside ( -FeSi 2 ) has received much attention for utilization in novel low-cost optoelectronic devices in part due to its various attractive physical properties [1][2][3]. It has been reported that -FeSi 2 can be epitaxially grown on Si with 2-5% lattice mismatches [4].…”
Section: Introductionmentioning
confidence: 99%